PENGARUH PELATIHAN PROGRAM KAMPUNG IKLIM ( PROKLIM ) TERHADAP PRODUKTIVITAS KERJA ( Studi Kelompok ANADOPAH Dusun Palasari Desa Sukahurip Kec.Cihaurbeuti Kab Ciamis): PENGARUH PELATIHAN PROGRAM KAMPUNG IKLIM ( PROKLIM ) TERHADAP PRODUKTIVITAS KERJA ( Studi Kelompok ANADOPAH Dusun Palasari Desa Sukahurip Kec.Cihaurbeuti Kab Ciamis) - Nur alvan, Eri; Wiwin Herwina; Nurlaila (Universitas Negeri Surabaya, 2025)
The current level of productivity of the Anadopah Group is in the low category. This is due to the low level of public understanding of the pro-climate program. Low application of knowledge in utilizing natural resources. This is one of the influences on increasing community productivity in this pro-climate program so that the Training Program becomes a solution to the problems that occur. So this research aims to determine the effect of Proklim training on the level of work productivity of the Anadopah group in Palasari hamlet. The research instrument used is a questionnaire containing statements that have been tested through validity and reliability tests. The data that has been collected has gone through a normality test, hestorescedescity test so that it can be continued to the hypothesis testing stage, including simple linear regression tests and determination tests (R square). ). The research results show that Proklim training has a positive and significant effect on increasing work productivity with a contribution of 53.7% while the remaining 46.3% is a contribution from other variables not included in this research model. Furthermore, the results of the analysis show a correlation value of 0.733. there is a strong relationship, so it can be concluded that pro-clim training has a positive and significant impact on the work productivity of the Anadopah group.